2016
DOI: 10.3892/ol.2016.4265
|View full text |Cite
|
Sign up to set email alerts
|

Role of perineural invasion as a prognostic factor in laryngeal cancer

Abstract: Abstract. The diffusion of laryngeal cancer cells in the perineural space is a parameter associated with a negative prognosis, high loco-regional recurrence and low disease-free survival rates. The spread of tumor cells on the perineural sheath highlights the histopathological and clinically aggressive behavior of this type of tumor, which may extend proximally or distally in the nerve for >10 cm. Therefore, the surgical resection margin is generally insufficient to treat patients with laryngeal cancer present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
1
14
0
3
Order By: Relevance
“…The presence of PNI was confirmed to have a significant negative impact in both uni- and multivariate analyses. This finding was previously reported by other authors [34,35,36,37]. In particular, Chirila et al analyzed a cohort of 256 patients treated for laryngeal and hypopharyngeal cancers and reported the presence of PNI in 35.6% of cases—which corresponds well with the rate observed herein—with a significant impact of minor nerve PNI on DSS and RFS [34].…”
Section: Discussionsupporting
confidence: 91%
“…The presence of PNI was confirmed to have a significant negative impact in both uni- and multivariate analyses. This finding was previously reported by other authors [34,35,36,37]. In particular, Chirila et al analyzed a cohort of 256 patients treated for laryngeal and hypopharyngeal cancers and reported the presence of PNI in 35.6% of cases—which corresponds well with the rate observed herein—with a significant impact of minor nerve PNI on DSS and RFS [34].…”
Section: Discussionsupporting
confidence: 91%
“…), for LC there are no specific and sensitive markers that can be used for early diagnosis and follow-up, beyond the available prognostic parameters 4 5 . Cell proliferative activity has been extensively investigated in head and neck tumours, including LC, as useful diagnostic and prognostic marker; however, its specific role has yet to be definitively established.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Perineural invasion influences recurrence, distant metastases, and survival in several head and neck sites, including the oropharynx, oral cavity, hypopharynx, and larynx. [13][14][15][16][17] Angiolymphatic invasion has received less attention than PNI, likely because it is difficult to recognize and has subsequently been omitted from some histologic grading systems. 9,18 Studies [18][19][20][21] have found an association between ALI and worse treatment outcomes; however, overall the literature is mixed, and additional studies to elucidate the significance of this association are indicated.…”
mentioning
confidence: 99%